1956
DOI: 10.1139/b56-066
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Fusarium Species in Canada: V. Taxonomy and Geographic Distribution of Fusarium Species in Soil

Abstract: A taxonomic study was made of 1348 isolates of Fusarium found in 206 soil samples collected in 1946. Approximately 70% of the samples, or 143, were obtained from 127 localities in Manitoba; the remaining 30%, or 63, came from seven other provinces.Of 25,973 colonies of fungi that developed on the 2060 soil-dilution plates involved in this study, Fusarium accounted for approximately 5%. A total of 14 species and varieties of Fusarium, classified in nine sections of the genus, were isolated; they are F. merismoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

1959
1959
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Since t h a t time he has isolated them from various habitats. Previous papers in this series have dealt nlith their identity and occurrence in two important habitats, ~lamely, agricultural seecls (2,3,4) and agricultural soils (5,6). The present paper is concerned primarily with the taxonomy and geographic distribution of those species, varieties, and forms of F i~s a~i z~n z Can.…”
Section: Introductionmentioning
confidence: 99%
“…Since t h a t time he has isolated them from various habitats. Previous papers in this series have dealt nlith their identity and occurrence in two important habitats, ~lamely, agricultural seecls (2,3,4) and agricultural soils (5,6). The present paper is concerned primarily with the taxonomy and geographic distribution of those species, varieties, and forms of F i~s a~i z~n z Can.…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of F. oxysporum in our samples agrees with other reports, which indicate that this species is the major pathogen of the fungal flora. For example, Gordon (1956) found that F. oxysporum was by far the most prevalent species of Fusarium spp., as it represented approximately 67% of Fusarium spp. In Canadian soil, Gordon (1956) showed that the relative abundance of the F. oxysporum might reach 3 -10% of the soil total fungal population.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gordon (1956) found that F. oxysporum was by far the most prevalent species of Fusarium spp., as it represented approximately 67% of Fusarium spp. In Canadian soil, Gordon (1956) showed that the relative abundance of the F. oxysporum might reach 3 -10% of the soil total fungal population. In the rhizosphere, the relative abundance of F. oxysporum may reach 43% of the total fungal population.…”
Section: Discussionmentioning
confidence: 99%
“…suggested that F. graminearum was unlikely to survive in soil without crop residues. Sutton (1982) indicated that soil is unlikely to be a 'major inoculum source' and referred to work by Gordon (1954Gordon ( , 1956 in Canada, where F. graminearum was not isolated from soil samples collected from cereal fields. In Australia, Wearing & Burgess (1977) isolated F. graminearum Group 1 (now known as F. pseudograminearum) from soil, but mainly associated with small pieces of debris.…”
Section: Introductionmentioning
confidence: 99%